Women in Mark's Gospel. By Susan Miller - Telford, William R. (The journal of theological studies, 2007)
A dissertation supervised by Joel Marcus, and originally submitted to the University of Glasgow in 2002, Susan Miller's book, published in 2004, is the fourth monograph to appear on this subject in fifteen years. The others are M. Fander's Die Stellung der Frau im Markusevangelium. Unter besonderer Berücksichtigung kultur- und religionsgeschichtlicher Hintergründe (Münsteraner Theologische Abhandlungen, 8; Altenberge: Telos, 1989), H. Kinukawa's Women and Jesus in Mark: A Japanese Feminist Perspective (Bible and Liberation; Maryknoll, NY: Orbis, 1994), and J. L. Mitchell's Beyond Fear and Silence: A Feminist-Literary Approach to the Gospel of Mark (New York and London: Continuum, 2001). The topic is, therefore, a popular one, as a plethora of recent articles also attests.